Novel Homozygous CYP27B1 Gene Mutation in Vitamin D-Dependent Rickets Type 1A (VDDR1A) Disorder: A Case Report - Al Homyani, Doua Khalid; Alhemaiani, Shahad Khalid (Frontiers in Endocrinology, 2022)
Background: Vitamin D-dependent rickets type 1A (VDDR1A) rickets is an uncommon kind of rickets that affects both boys and girls. Genetic testing by a highly suspicious doctor is required for the ultimate diagnosis Case Presentation: This is a case report of VDDR1A in a 4-year-old boy who presented with delayed growth, inability to stand, and rachitic bone deformities. The diagnosis was reached by anthropometric measurement, bone profile, and radiological studies then confirmed by genetic testing which revealed a homozygous pathogenic variant in the CYP27B1 gene. He was treated with Vitamin-D analogs and oral and oral calcium. Conclusion: VDDR1A is caused by a mutation in the CYP27B1 gene, which impairs the 1 hydroxylase enzyme, which compromises vitamin-D production. Keywords: VDDR1A, CYP27B1 gene, dependent rickets, 1,25-dihydroxyvitamin D, 25 hydroxyvitamin D.